Mobility of A Water Droplet on Liquid Phase of N-Octadecane Coated Hydrophobic Surface. Issue 1 (December 2018) - Yilbas, Bekir; Ali, Haider; Al-Sharafi, Abdullah; Al-Aqeeli, Nasser; Abu-Dheir, Numan; Demir, Kahraman
Abstract A water droplet behavior on the liquid n-octadecane film is investigated. The coating of hydrophobic surface by N-octadecane film provides exchange of wetting state on the surface. The polycarbonate surface is crystallized and the functionalized silica particles are placed on the resulting surface prior to thin film coating of n-octadecane. A high-speed camera is used to monitor dynamic characteristics of the droplet on the inclined film. The findings reveal that deposition of thin n-octadecane film on hydrophobic surface results in reversibly exchange of the wetting state at the surface, which remains hydrophobic when n-octadecane film is in solid phase while it becomes hydrophilic when n-octadecane film liquefies. Droplet transition velocity predicted agrees well with the experimental data. Sliding mode of the water droplet governs droplet transition on the liquid surface. Droplet pinning force, due to interfacial tension, dominates over the other retention forces including drag and shear.